Azo-PROTAC: Novel Light-Controlled Small-Molecule Tool for Protein Knockdown - Jin, Yu-Hui; Lu, Meng-Chen; Wang, Yan; Shan, Wen-Xin; Wang, Xuan-Yu; You, Qi-Dong; Jiang, Zheng-Yu (Journal of medicinal chemistry, 2020)
Reversibly altering endogenous protein levels are persistent issues. Herein, we designed photoswitchable azobenzene-proteolysis targeting chimeras (Azo-PROTACs) by including azobenzene moieties between ligands for the E3 ligase and the protein of interest. Azo-PROTACs are light-controlled small-molecule tools for protein knockdown in cells. The light-induced configuration change can switch the active state to induce protein degradation activity, which can be reversely controlled by light exposure in intact cells. We compared the protein degradation abilities of Azo-PROTACs with different configurations and linker lengths. Using the stable form with the best degradation ability against the BCR-ABL fusion and ABL proteins in myelogenous leukemia K562 cells, we showed that Azo-PROTAC combines the potent protein knockdown and facile cell uptake properties of the small-molecule PROTAC with a reversible photoswitchability, offering a promising chemical knockdown strategy based on the light-induced reversible on/off properties.